Educational activity in middle adulthood and in the context of a family biography - Przybylska, Izabela (Biografie rodzinne i uczenie się: Tom 8, 2021)
The text presents the analysis and interpretation of the biography of a 57-year-old woman described from the educational perspective and within the family space. The aim of the study was to investigate how an adult understands learning and how it shapes their adulthood, to determine the relationship between their educational activity and development, to distinguish learning in a family biography and to find an image of the family present in this biography. I obtained the data by conducting a biographical narrative interview. The analysis of the interview I conducted with the respondent has led me to formulate the following categories: the complexity of motivation, the influence and role of the family in shaping her identity and the consequences of these interactions interpreted from the perspective of the learning process in the family, school trauma, a biographical breakthrough and the process of change, the value of educational activity and its outcomes. Moreover, I indicate the links between this activity and the experiences of earlier periods of the respondent’s life dating back to her early childhood. The educational biograph I analysed is the basis for reflection on the search for the fullness of life, personal and professional development rooted in a family biography, and creative becoming from the perspective of lifelong learning.